Green Economy and Green Jobs Development in Indonesia - Ma‟ruf, Ahmad; Farahdita, Lula (Prosiding University Research Colloquium, 2018)
The utilization and development of environment-friendly renewable energy are becoming increasingly important given the increasingly limited fossil energy sources or non-renewable energy sources. The problem in this study is how to develop a Green Job in support of realizing Green Energy in Indonesia.This study is qualitative research with descriptive analysis. Green Energy is one step to realize a Green Economy. In practice, the required human resources also support and in line with the context of the Green Economy and Green Energy, i.e. Green Jobs. Development opportunities Green Jobs in the energy sector is very large, but the phenomenon of Green Jobs in Indonesia is still relatively new, therefore the participatory processes in policy development and implementation that supports it is absolutely necessary, and also with the promotion.